Analisis Faktor Yang Memengaruhi Intensi Menggunakan Fintech Syariah: Studi Empiris Generasi Milenial Tangerang Raya - Elif Pardiansyah; Najmudin Najmudin; Ahmad Fatoni (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
Indonesia has experienced a significant increase in internet penetration over the past decade. The implications of increasing internet penetration have an impact on business patterns in various industrial lines. Financial technology (fintech) is proof of the implementation of a financial system by delivering more efficient financial services. Fintech has an important role in financial intermediation and helps the daily lives of almost all people in the world. Fintech has changed the way consumers conduct financial transactions. This study aims to find out what factors underlie behavioral intentions to use sharia fintech in the millennial generation in Tangerang Raya. This study uses the technology acceptance model (TAM) and accommodates a new variable, namely religiosity. The sampling technique used purposive sampling so that a total sample of 237 respondents was obtained online using the Google form. This study was analyzed using multiple linear regression using SPSS 22 software. The results of this study indicate that the intention to use the millennial generation of sharia fintech in Tangerang Raya is influenced by the perceived usefulness factor with a P-value of 0.00 <0.05, and the Islamic religiosity variable with a P-value of 0.00 <0.05. Meanwhile, perceived ease of use does not have a significant effect on the intention to use fintech at the sig 5% level with a p-value of 0.197 > 0.05.